Physical, physiological, technical and tactical responses according to the playing position in male basketball: a systematic scoping review - Martinho, D. V.; Clemente, F. M.; Gomez, M.-Á.; Rebelo, A.; Field, A.; Santos, C. C.; Gouveia, É. R.; Afonso, J.; Sarmento, H. (Journal of Human Kinetics, 2025)
Understanding how playing position influences physical, physiological, technical, and tactical demands in basketball is essential for optimizing training. Despite numerous studies examining these demands, there remains a need for a comprehensive review focused specifically on male basketball players. This scoping review aimed to summarize these demands during training sessions and games among male professional and semiprofessional basketball players according to playing positions. Following the PRISMA guidelines and its extensions for scoping reviews, four databases (PubMed, Scopus, SPORTDiscus, and Web of Science) were searched. Studies were included if they featured male professional or semiprofessional basketball players, assessments during training or games, and reported relevant demands. Forty-seven manuscripts were reviewed. Key findings revealed notable differences between positions: (i) guards covered greater distances, performing more accelerations and decelerations compared to forwards and centers; (ii) forwards engaged in more high-speed and high-intensity running; (iii) centers demonstrated higher averages in successful shots and rebounds; and (iv) physiological responses, particularly heart rate, were predominantly higher among centers. In conclusion, this review provides coaches with critical insights into position-specific physical and physiological demands in basketball. Notably, methodological inconsistencies across the studies reviewed were observed. Hence, establishing standardized assessment methodologies and creating a common framework for normalizing physical, physiological, technical, and tactical variables is crucial for enhancing research comparability and practical application.